Complete Genome Sequencing and Targeted Mutagenesis Reveal Virulence Contributions of Tal2 and Tal4b of Xanthomonas translucens pv. undulosa ICMP11055 in Bacterial Leaf Streak of Wheat - Falahi Charkhabi, Nargues; Booher, Nicholas J.; Peng, Zhao; Wang, Li; Rahimian, Heshmat; Shams-Bakhsh, Masoud; Liu, Zhaohui; Liu, Sanzhen; White, Frank F.; Bogdanove, Adam J. (Frontiers in Microbiology, 2017)
Bacterial leaf streak caused by Xanthomonas translucens pv. undulosa (Xtu) is an important disease of wheat (Triticum aestivum) and barley (Hordeum vulgare) worldwide. Transcription activator-like effectors (TALEs) play determinative roles in many of the plant diseases caused by the different species and pathovars of Xanthomonas, but their role in these diseases has not been characterized. ICMP11055 is a highly virulent Xtu strain from Iran. The aim of this study was to better understand genetic diversity of Xtu and to assess the role of TALEs in bacterial leaf streak of wheat by comparing the genome of this strain to the recently completely sequenced genome of a U.S. Xtu strain, and to several other draft X. translucens genomes, and by carrying out mutational analyses of the TALE (tal) genes the Iranian strain might harbor. The ICMP11055 genome, including its repeat-rich tal genes, was completely sequenced using single molecule, real-time technology (Pacific Biosciences). It consists of a single circular chromosome of 4,561,583 bp, containing 3,953 genes. Whole genome alignment with the genome of the US Xtu strain XT4699 showed two major re-arrangements, nine genomic regions unique to ICMP11055, and one region unique to XT4699. ICMP110055 harbors 26 non-TALE type III effector genes and seven tal genes, compared to 25 and eight for XT4699. The tal genes occur singly or in pairs across five scattered loci. Four are identical to tal genes in XT4699. In addition to common repeat-variable diresidues (RVDs), the tal genes of ICMP11055, like those of XT4699, encode several RVDs rarely observed in Xanthomonas, including KG, NF, Y*, YD, and YK. Insertion and deletion mutagenesis of ICMP11055 tal genes followed by genetic complementation analysis in wheat cv. Chinese Spring revealed that Tal2 and Tal4b of ICMP11055 each contribute individually to the extent of disease caused by this strain. A largely conserved ortholog of tal2 is present in XT4699, but for tal4b, only a gene with partial, fragmented RVD sequence similarity can be found. Our results lay the foundation for identification of important host genes activated by Xtu TALEs, as targets for the development of disease resistant varieties.